Determination of the through‐plane profile of vanadium species in hydrated Nafion studied with micro X‐ray absorption near‐edge structure spectroscopy – proof of concept. (2nd November 2021) - Lutz, Christian; Hampel, Sven; Beuermann, Sabine; Turek, Thomas; Kunz, Ulrich; Garrevoet, Jan; Falkenberg, Gerald; Fittschen, Ursula
Abstract : The profiles of vanadium species inside hydrated Nafion membranes have been determined using micro X‐ray absorption near‐edge structure spectroscopy. This proof of concept study shows how to optimize the procedure with respect to spatial resolution, statistics and species preservation. Abstract : Vanadium‐ion transport through the polymer membrane results in a significant decrease in the capacity of vanadium redox flow batteries. It is assumed that five vanadium species are involved in this process. Micro X‐ray absorption near‐edge structure spectroscopy (micro‐XANES) is a potent method to study chemical reactions during vanadium transport inside the membrane. In this work, protocols for micro‐XANES measurements were developed to enable through‐plane characterization of the vanadium species in Nafion 117 on beamline P06 of the PETRA III synchrotron radiation facility (DESY, Hamburg, Germany). A Kapton tube diffusion cell with a diameter of 3 mm was constructed. The tube diameter was chosen in order to accommodate laminar flow for cryogenic cooling while allowing easy handling of the cell components by hand. A vertical step size of 2.5 µm and a horizontal step size of 5 µm provided sufficient resolution to resolve the profile and good statistics after summing up horizontal rows of scan points. The beam was confined in the horizontal plane to account for the waviness of the membrane. The diffusion of vanadium ions during measurement was inhibited by the cryogenic cooling. Vanadium oxidation, e.g. by water radiolysis (water percentage in the hydrated membrane ∼23 wt%), was mitigated by the cryogenic cooling and by minimizing the dwell time per pixel to 5 ms. Thus, the photo‐induced oxidation of V 3+ in the focused beam could be limited to 10%. In diffusion experiments, Nafion inside the diffusion cell was exposed on one side to V 3+ electrolyte and on the other side to VO2 + . The ions were allowed to diffuse across the through‐plane orientation of the membrane during one of two short defrost times (200 s and 600 s). Subsequent micro‐XANES measurements showed the formation of VO 2+ from V 3+ and VO2 + inside the water body of Nafion. This result proves the suitability of the experimental setup as a powerful tool for the determination of the profile of vanadium species in Nafion and other ionomeric membranes.